2017
DOI: 10.1155/2017/3675848
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Cause of Intestinal Obstruction in a Young Adult Patient: Inflammatory Fibroid Polyp

Abstract: Inflammatory fibroid polyps are uncommon benign lesions that originate in the submucosa of the gastrointestinal tract. The stomach and the ileum are the most commonly affected sites. Although inflammatory fibroid polyp is one of the rare conditions leading to intestinal obstruction in adults, it should be considered as a possible diagnosis in obstructive tumors of the small bowel causing intussusceptions. We present one case of inflammatory fibroid polyp as a rare cause of intussusception in a young adult pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the gastrointestinal tract, IFPs can originate in various locations. They mostly occur in the gastric antrum (66%–75%) [ 1 ] followed by small bowel (18%–20%), with 4%–7% in the colorectal region, and 1% in the esophagus, duodenum, gallbladder and appendix each [ 8 ]. In a case series study of 76 patients by Johnstone and Morson revealed that 18% of IFPs were present in the small bowel [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the gastrointestinal tract, IFPs can originate in various locations. They mostly occur in the gastric antrum (66%–75%) [ 1 ] followed by small bowel (18%–20%), with 4%–7% in the colorectal region, and 1% in the esophagus, duodenum, gallbladder and appendix each [ 8 ]. In a case series study of 76 patients by Johnstone and Morson revealed that 18% of IFPs were present in the small bowel [ 14 ].…”
Section: Discussionmentioning
confidence: 99%